2014
DOI: 10.1039/c4ra10697k
|View full text |Cite
|
Sign up to set email alerts
|

New mixed-ligand cyanohydroxo octahedral cluster complex trans-[Re6S8(CN)2(OH)4]4−, its luminescence properties and chemical reactivity

Abstract: A new mixed-ligand anionic cluster complex trans-[Re6S8(CN)2(OH)4]4− has been synthesized and characterized by different physical methods. In addition, two representative reactions confirming the composition and structure of the anion have been carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The bonds lengths in cluster complexes vary in the following ranges: d (Re–Re) = 2.5939(11)–2.6124(11) Å in 1 and 2.6218(10)–2.6360(10) Å in 2 , d (Re−μ 3 -Q) = 2.397(3)–2.413(4) Å in 1 and 2.5062(12)–2.5173(14) Å in 2 , d (Re–S SO 3 ) = 2.464(3) Å in 1 and 2.463(3) Å in 2 ; d (S–O) = 1.487(11)–1.513(12) Å in 1 and 1.484(10)–1.492(10)­Å in 2 . The bond lengths within the cluster cores {Re 6 S 8 } 2+ (in 1 ) and {Re 6 Se 8 } 2+ (in 2 ) are in good agreement with those reported earlier for hexarhenium cluster complexes with various apical ligands. , At the same time, Re–S SO3 and S–O bond lengths correlate well with those found in [{Re 12 CS 17 }­(SO 3 ) 6 ] 12– …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The bonds lengths in cluster complexes vary in the following ranges: d (Re–Re) = 2.5939(11)–2.6124(11) Å in 1 and 2.6218(10)–2.6360(10) Å in 2 , d (Re−μ 3 -Q) = 2.397(3)–2.413(4) Å in 1 and 2.5062(12)–2.5173(14) Å in 2 , d (Re–S SO 3 ) = 2.464(3) Å in 1 and 2.463(3) Å in 2 ; d (S–O) = 1.487(11)–1.513(12) Å in 1 and 1.484(10)–1.492(10)­Å in 2 . The bond lengths within the cluster cores {Re 6 S 8 } 2+ (in 1 ) and {Re 6 Se 8 } 2+ (in 2 ) are in good agreement with those reported earlier for hexarhenium cluster complexes with various apical ligands. , At the same time, Re–S SO3 and S–O bond lengths correlate well with those found in [{Re 12 CS 17 }­(SO 3 ) 6 ] 12– …”
Section: Resultssupporting
confidence: 89%
“…The lability of apical ligands in hydroxo and aqua-hydroxo hexarhenium cluster complexes was previously demonstrated. In particular, it has been shown that ligands can be replaced in a molten proligand or in an aqueous solution containing a suitable nucleophile. , Continuing to investigate the reactivity of these complexes, we studied the reaction of aqua-hydroxo-complexes with sulfite ions in an aqueous solution. It was found that at room temperature the reaction did not proceed, the solution remained colorless.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we and others have developed a cluster-based Lewis acidic platform for synthetically meaningful transformations. Specifically, the octahedral cluster core of [Re 6 (μ 3 -Se) 8 ] 2+ , being Lewis acidic because of the 2+ charge, has been found to support a great variety of aerobically stable complexes. with some of the ligands being activated for further reactions. In our work, with triethylphosphino (PEt 3 ) ligands occupying and passivating some of the Re sites, cluster-bound acetonitrile (CH 3 CN) undergoes stereospecific and atom economical nucleophilic addition with methanol and ethanol, affording the corresponding imino ester complexes. , Szczepura and co-workers, on the other hand, reported the addition of N 3 – to nitrile(s) bound to the same cluster core to produce tetrazolate complexes in a click-chemistry fashion. , We later showed that the nitrile ligand can also be exchanged for organic azides, and subsequent decomposition of the azido cluster complexes upon ultraviolet irradiation produced the corresponding imino complexes in a stereospecific fashion. , Besides the cluster–nitrile complexes, we have also succeeded in the preparation of the carbonyl complexes of the same cluster core. Such cluster carbonyls are similar to the classical organometallic carbonyls in terms of their back-bonding electronic structure, with the cluster-bound CO ligand(s) being activated for further transformations.…”
mentioning
confidence: 77%
“…The chemistry of chalcogenide-capped octahedral hexanuclear rhenium complexes with six terminal ligands has been well studied: the complex has 24 d electrons (24e), and the oxidation state of each rhenium ion is +3. The complex unit is intriguing because it exhibits rich redox and photoluminescent properties. , The terminal ligands on the complex are moderately inert to a substitution reaction, which results in stepwise ligand substitutions at the terminal positions. ,,, The complex unit undergoes one-electron oxidation, and the Re 6 (23e)/Re 6 (24e) process is dependent on the nature of the terminal ligands. ,,, The one-electron oxidation process of [Re 6 (μ 3 -S) 8 Cl 6 ] 4– (0.31 V vs Ag/AgCl) shifts positively upon substitution of the terminal chloride ligands with pyridine (py), leading to show at 0.77 V for trans -/ cis -[Re 6 (μ 3 -S) 8 Cl 4 (py) 2 ] 2– or 1.03 V for [Re 6 (μ 3 -S) 8 Cl 3 (py) 3 ] − . A trend similar to that mentioned above has also been observed for [Re 6 (μ 3 -S) 8 Cl 6– n (PEt 3 ) n ] n −4 (PEt 3 : triethylphosphine, n = 1–4) .…”
Section: Introductionmentioning
confidence: 99%
“…Sulfide-capped octahedral hexanuclear rhenium­(III) complexes exhibit photoluminescence in the solid state and in solution. , , ,,, , ,,,, , , The photoemissive excited triplet states of these complexes can be classified into two types: cluster core-centered ( 3 CC) and cluster core-to-L charge-transfer [more generally metal-to-ligand charge-transfer ( 3 MLCT)] states. Most octahedral hexanuclear complexes generate the relevant 3 CC states upon photoexcitation.…”
Section: Introductionmentioning
confidence: 99%